Crop associations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
More than 800 publications on crop associations have been brought together in a publication of the German Agency for Technical Cooperation, GTZ. Both recent and older publications are included, which makes this collection of significant value for...